Pengaruh Karakteristik Individu, Fasilitas Kerja dan Teamwork terhadap Produktivitas Kerja Pegawai - Oktapiadewi, I Gusti Ayu Eka; Astawa, I Putu Putra; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Enhancing employee efficiency stands as a critical managerial hurdle, as the attainment of objectives and the sustenance of a company hinge upon the caliber of its workforce. This study aims to assess the determinants impacting the productivity of Civil Servants (PNS) stationed at the Office of Population and Civil Registration in Klungkung Regency. A total of 36 employees were sampled using a comprehensive approach at the aforementioned office. Data gathering was accomplished through the administration of questionnaires. Employing multiple linear regression analysis, this study examines the effects of Individual Characteristics, Work Facilities, and Teamwork on employee productivity within the Office of Population and Civil Registration in Klungkung Regency.The results of hypothesis testing show that Individual Characteristics, Work Facilities, and Teamwork have a significant positive effect both partially and simultaneously on Employee Productivity at the Office of Population and Civil Registration of Klungkung Regency. Therefore, it is recommended that the office improve employee productivity through discipline training, strict supervision, and the development of a work culture that values ??values. Evaluation and improvement of office facilities are also needed to enhance comfort and productivity. For further research, it is recommended to expand the sample, conduct research in different locations, and consider additional variables such as motivation and leadership for a deeper understanding of the factors influencing employee productivity.